NILAI EKSAK BILANGAN DOMINASI COMPLEMENTARY TREE TERHUBUNG-3 PADA GRAF CYCLE, GRAF LENGKAP DAN GRAF WHEEL - Agustiarini, Efni; Ratnasari, Lucia; ., Widowati (MATEMATIKA, 2015)
Given a graph G with a set of vertices V and the set of edges E. Let  be a subset of , if each vertex of  is adjacent to at least one vertex of , then  is called a dominating set in . The domination number of a graph  denoted as  is the minimum cardinality taken from all dominating sets of . Sometypes of dominating set has been developed based on domination perameter, such as connected dominating set, triple connected dominating set, complementary tree dominating set and triple connected complementary tree dominating set. A subset  with , a nontrivial connected graph is said to be triple connected complementary tree dominating set, if  dominating set,  is a triple connected graph and  is a tree. The triple connected complementary tree domination number of G is denoted as  In this paper we study about triple connected complementary tree domination number, especially on the cycle graph, complete graph and wheel graph. For any cycle graph and complete graph of order  have . For any wheel graph of order  have